The Mediterranean Botany section on ethnobotany and ethnopharmacology: required standards for articles based on field research - Benítez, Guillermo; Pardo de Santayana, Manuel; Rivera, Diego; Verde, Alonso; Gras, Airy; Gavilán, Rosario G. (Mediterranean Botany, 2022)
In this new era of Mediterranean Botany, the editorial team opened the possibility of submitting manuscripts for evaluation to the ethnobotany/ethnopharmacology section of the journal. We present a compendium of the minimum standards that manuscripts based in field research should comply in order to positively pass to the review process, as a minimum quality requirement. We pay special attention to the contents that should be included in the method and results sections, which are often the ones that present problems of format, style or content. Without being in any way exhaustive in the listed standards, we believe that these recommendations will help authors to present their texts and reviewers to evaluate them.